Slurry and preparation method thereof, electrode and battery
By using a combination of solvents with different wetting properties and boiling points in heterojunction cell paste, the flow and collapse of the paste during printing and curing is solved, and a high aspect ratio and efficient photoelectric conversion efficiency are achieved.
Patent Information
- Application Number
- CN202411941198.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-11
AI Technical Summary
The existing heterojunction battery paste has problems such as flow and collapse during screen printing and curing, resulting in wide and low linear shapes, affecting the photoelectric conversion efficiency.
By using different types of solvents, and combining two or more solvents with different wetting properties and boiling points, the shaping ability of the slurry is enhanced, the aspect ratio of printing is improved, and the conductivity of the slurry after curing is improved.
The slurry is realized to keep the linear full and not collapsed when printed on the solar cell, and the height and aspect ratio reaches more than 0.5, which improves the photoelectric conversion efficiency of the battery, and adapts to the 18 micron and finer screen openings to achieve fine printing.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a slurry and a preparation method thereof, an electrode and a battery. Background Art
[0002] Screen printing is the most commonly used process in solar cells due to its low cost and easy operation. However, due to the strong fluidity and unstable curing rate of heterojunction battery paste on the market, there are problems such as flow and collapse during screen printing and paste curing, which makes the line shape wide and low, affecting the photoelectric conversion efficiency.
[0003] Therefore, while ensuring the conductive efficiency, it is of utmost importance to make the paste have good screen printability, plasticity and high aspect ratio. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to provide a slurry and a preparation method thereof, an electrode and a battery. The slurry of the present application can enhance the shaping ability of the slurry by using different types of solvents, improve the aspect ratio of the slurry printing, thereby improving the conductivity of the slurry after curing, and then improve the photoelectric conversion efficiency of the battery.
[0005] In the first aspect of the present application, the present application proposes a slurry. According to an embodiment of the present application, the slurry includes: a conductive powder, a thermosetting component, a curing agent and a mixed solvent, wherein the mixed solvent includes two or more solvents with different wettability and different boiling points. The inventors found in experiments that by selecting and combining two or more solvents with different wettability and different boiling points, the shaping properties of the slurry can be enhanced. This optimized solvent combination enables the slurry to maintain a full linear shape without collapse when printed on a solar cell, thereby achieving an aspect ratio of more than 0.5. This improvement not only improves the conductivity of the slurry after curing and the photoelectric conversion efficiency of the battery, but also enables the slurry to adapt to screen openings of 18 microns and finer, achieving fine printing.
[0006] According to an embodiment of the present application, the slurry may further include at least one of the following additional technical features:
[0007] According to an embodiment of the present application, based on the total mass of the slurry, the mass proportion of the mixed solvent is 2%-10%.
[0008] According to an embodiment of the present application, based on the total mass of the slurry, the mass proportion of the conductive powder is 92%-94%.
[0009] According to an embodiment of the present application, based on the total mass of the slurry, the mass proportion of the thermosetting component is 1%-10%.
[0010] According to an embodiment of the present application, based on the total mass of the slurry, the mass proportion of the curing agent is 0.2%-1.5%.
[0011] According to an embodiment of the present application, the mixed solvent includes at least two of a first solvent, a second solvent, and a third solvent; the diffusion radius of the first solvent on the battery cell is less than 0.9 cm, and the boiling point is higher than 245°C; the diffusion radius of the second solvent on the battery cell is 0.9-1.1 cm, and the boiling point is 225°C-245°C; the diffusion radius of the third solvent on the battery cell is higher than 1.1 cm, and the boiling point is lower than 225°C.
[0012] According to an embodiment of the present application, the first solvent includes at least one of carbitol butyl ether acetate, dibasic acid ester (DBE), 2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester, tripropylene glycol monobutyl ether, and tripropylene glycol methyl ether.
[0013] According to an embodiment of the present application, the second solvent includes acetic acid ester of glycol ether.
[0014] According to an embodiment of the present application, the glycol ether acetate includes at least one of 3-hydroxy-3-carboxyglutarate tributyl ester and diethylene glycol butyl ether acetate.
[0015] According to an embodiment of the present application, the third solvent includes at least one of terpineol, diethylene glycol diethyl ether, butyl carbitol (diethylene glycol monobutyl ether), cyclohexanone, and methyl ethyl ketone.
[0016] According to an embodiment of the present application, the slurry further includes an auxiliary agent.
[0017] According to an embodiment of the present application, the conductive powder includes at least one of silver powder and silver-coated metal powder.
[0018] According to an embodiment of the present application, the thermosetting component includes at least one of a bisphenol epoxy resin and an alicyclic epoxy resin.
[0019] According to an embodiment of the present application, the curing agent includes at least one of a thermal cationic curing agent and a blocked polyisocyanate curing agent.
[0020] According to an embodiment of the present application, the auxiliary agent includes at least one of a silane coupling agent, a stabilizer, a dispersant, and an epoxy diluent.
[0021] According to an embodiment of the present application, the conductive powder includes the silver powder and the silver-coated metal powder, and the mass ratio of the silver powder to the silver-coated metal powder is (20:80)-(30:70).
[0022] According to an embodiment of the present application, the thermosetting component includes the bisphenol epoxy resin and the alicyclic epoxy resin, and the mass ratio of the bisphenol epoxy resin to the alicyclic epoxy resin is (60:40):(80:20).
[0023] According to an embodiment of the present application, the curing agent includes a thermal cationic curing agent and a blocked polyisocyanate curing agent, wherein, based on the total mass of the slurry, the mass proportion of the thermal cationic curing agent is 0.1%-1%, and the mass proportion of the blocked polyisocyanate curing agent is 0.1%-0.5%.
[0024] According to an embodiment of the present application, the blocked polyisocyanate curing agent is a compound formed by blocking a polyisocyanate compound.
[0025] In the second aspect of the present application, the present application proposes a method for preparing the slurry described in the first aspect. According to an embodiment of the present application, the method comprises: mixing a conductive powder, a thermosetting component, a curing agent and a mixed solvent; grinding the mixed product to obtain the slurry; wherein the mixed solvent comprises two or more solvents with different wettability and different boiling points. By adopting the method described in the present application, a slurry with high plasticity can be prepared. The slurry can be used for printing to make the line type full and not collapsed, and the aspect ratio of the printing can be improved, thereby improving the photoelectric conversion efficiency of the battery; in addition, the slurry can adapt to 18 microns and finer screen openings to achieve fine printing. Those skilled in the art can understand that this method has all the characteristics and advantages of the slurry described above, and will not be elaborated here.
[0026] In the third aspect of the present application, the present application proposes an electrode. According to an embodiment of the present application, the electrode is formed by curing the slurry prepared by the slurry described in the first aspect or the method described in the second aspect. As mentioned above, the slurry of the present application has a high plasticity and can improve the aspect ratio of the printing to more than 0.5, thereby improving the conductivity of the electrode formed after the slurry is cured, thereby improving the photoelectric conversion efficiency of the battery. It can be understood by those skilled in the art that the electrode has all the characteristics and advantages of the slurry described above, and no further elaboration is given here.
[0027] In the fourth aspect of the present application, the present application proposes a battery. According to an embodiment of the present application, the battery includes the electrode described in the third aspect. As mentioned above, the slurry of the present application has a high plasticity, which can improve the aspect ratio of the printing to more than 0.5, thereby improving the conductivity of the electrode formed after the slurry is cured, and then the photoelectric conversion efficiency of the battery can be improved. It can be understood by those skilled in the art that the battery has all the features and advantages of the electrodes described above, and no further elaboration is given here.
[0028] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION
[0029] The embodiments of the present application are described in detail below, which are intended to be used to explain the present application but should not be construed as limiting the present application.
[0030] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0031] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the description and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.
[0033] In this document, the terms "include" or "comprising" are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0034] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.
[0035] In the prior art, the aspect ratio is a very important indicator in heterojunction battery paste. The grid lines of the battery cells are getting thinner and thinner. Some manufacturers in the industry have begun to try to use screen-printed grid lines with an opening of 18μm to reduce the grid lines from blocking sunlight, increase the short-circuit current, and increase the conversion efficiency of the battery cells. Under the same grid line height, the thinner the grid line, the greater the resistance, which affects the conversion efficiency. Therefore, a larger aspect ratio is conducive to improving the conversion efficiency. The aspect ratio of the existing paste is not good, mainly because it is necessary to balance two factors, one is the leveling of the paste, and the other is the plasticity. If the plasticity is too good, the paste loses fluidity, and the lines after printing are very high in some places and very low in some places, with almost no paste; if the leveling is too good, the silver paste cannot stand up on the silicon wafer, and collapses and flows like water. It is precisely because of the mutual constraints of these two aspects that the aspect ratio cannot be very high. At present, the aspect ratio of the silver paste of DuPont, the best in the world, can only be about 0.4.
[0036] There are several common methods to improve the aspect ratio of slurry printing. Among them, epoxy resin, polyurethane and aliphatic epoxy resin can be compounded to increase the viscosity of the slurry and thus improve the plasticity; or appropriate amounts of surfactants, thixotropic agents and other additives can be added to improve the thixotropic properties of the slurry, thereby achieving the purpose of shaping. However, these measures will affect the electrical properties of the slurry while changing the viscosity of the slurry.
[0037] Based on this, in order to improve the plasticity of the slurry, the inventors of this application conducted relevant research on the formula of the slurry and found that by using solvents with different wettability and boiling points, the shaping ability of the slurry can be enhanced, and when it is printed on a heterojunction cell, a full and non-collapsed line shape can be obtained, and the aspect ratio can reach more than 0.5, and it is suitable for fine line printing with a screen opening of 18μm or less. The slurry and its preparation method, electrode and battery are described in detail below.
[0038] Slurry
[0039] The present application proposes a slurry. According to an embodiment of the present application, the slurry includes: a conductive powder, a thermosetting component, a curing agent and a mixed solvent, wherein the mixed solvent includes two or more solvents with different wettability and different boiling points. The inventors found in the experiment that the shaping performance of the slurry can be enhanced by selecting and combining two or more solvents with different wettability and different boiling points. Among them, the use of two solvents with different wettability can regulate the overall wettability of the mixed solvent, thereby improving the compatibility of the slurry with the substrate surface, effectively reducing the excessive flow of the slurry during the printing process, thereby improving the printing quality; in addition, solvents with different boiling points evaporate at different rates during the drying process of the slurry, which helps to maintain the stability of the volatilization of the mixed solvent during the entire drying process, prevent the slurry from collapsing during the curing process, further enhance the shaping ability of the slurry, and improve the printing aspect ratio. As a result, this optimized solvent combination enables the slurry to maintain a full linear shape and not collapse when printed on a solar cell, thereby achieving an aspect ratio of more than 0.5. This improvement not only improves the conductivity of the slurry after curing and the photoelectric conversion efficiency of the battery, but also enables the slurry to adapt to screen openings of 18 microns and finer, achieving fine printing.
[0040] In some embodiments of the present application, the solvents of the present application are divided into three categories according to the boiling point and wettability of the solvent: the first solvent is a high boiling point with low wettability, the second solvent is a medium boiling point with medium wettability, and the third solvent is a low boiling point with high wettability. Among them, the definition of the wettability of the solvent is the rate at which a drop of solvent diffuses to the surrounding area on the heterojunction cell per unit time. The diffusion rate is reflected by the diffusion radius. When the diffusion radius is 0.9cm-1.1cm, it is defined as moderate wettability, below 0.9cm is poor wettability, and above 1.1cm is good wettability. In addition, the boiling point of the solvent is defined as a medium boiling point between 225-245°C, above 245°C is a high boiling point, and below 225°C is a low boiling point.
[0041] In some embodiments of the present application, the mixed solvent includes at least two of the first solvent, the second solvent, and the third solvent; the diffusion radius of the first solvent on the battery cell is lower than 0.9 cm, and the boiling point is higher than 245°C; the diffusion radius of the second solvent on the battery cell is 0.9-1.1 cm, and the boiling point is 225°C-245°C; the diffusion radius of the third solvent on the battery cell is higher than 1.1 cm, and the boiling point is lower than 225°C. It should be noted that the "diffusion radius on the battery cell" refers to the diffusion radius of a drop of the solvent on the heterojunction battery cell within one minute.
[0042] In some embodiments of the present application, the first solvent includes at least one of carbitol butyl ether acetate, divalent acid ester (DBE), 2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester, tripropylene glycol monobutyl ether, and tripropylene glycol methyl ether. In some embodiments of the present application, the second solvent includes an acetate of glycol ethers. According to an embodiment of the present application, the acetate of glycol ethers includes at least one of 3-hydroxy-3-carboxyglutaric acid tributyl ester and diethylene glycol butyl ether acetate. In some embodiments of the present application, the third solvent includes at least one of pineneol, diethylene glycol diethyl ether, butyl carbitol (diethylene glycol monobutyl ether), cyclohexanone, and methyl ethyl ketone. Thus, by arbitrarily combining three different types of solvents, not only the fluidity and shaping ability of the slurry are guaranteed, so that it has an excellent aspect ratio, but also it can be adapted to 18 microns and finer screen openings to achieve fine printing.
[0043] In some embodiments of the present application, when the total amount of each component of the slurry is taken as 100 parts by mass, the mass proportion of the mixed solvent based on the total mass of the slurry is 2%-10%. For example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., or it can be a range composed of any of the above numerical values. Thus, the slurry can have good viscosity and fluidity. In addition, it is necessary to avoid excessive solvent content, which leads to low viscosity of the slurry and poor slurry forming ability, and to avoid too little solvent content, which leads to excessive viscosity of the slurry, loss of shear fluidity under conventional construction processes, and difficulty in use.
[0044] It should be noted that when the mixed solvent is selected from any two or more of the first solvent, the second solvent, and the third solvent, the volume ratio of any two solvents or three solvents is not particularly limited in the present application, and can be added to a degree that the wettability of the solvent and the fluidity of the slurry can be adjusted to a suitable range. Exemplarily, the volume ratio of any two reagents is (1:9)-(9:1), for example, it can be 1:9, 1:4, 3:7, 2:3, 1:1, 3:2, 7:3, 4:1, 9:1, etc., or it can be the range composed of any of the above numerical values. Exemplarily, the volume ratio of the three reagents is: (1-9): (1-9): (1-9), for example, it can be 1:1:1, 1:1:2, 1:1:3, 1:2:3, 2:2:3, 5:2:3, 1:2:7, etc., or it can be the range composed of any of the above numerical values.
[0045] In some embodiments of the present application, based on the total mass of the slurry, the mass proportion of the conductive powder is 92%-94%. For example, it can be 92%, 92.5%, 93%, 93.5%, 94%, etc., or it can be a range composed of any of the above numerical values. Thus, by making the mass proportion of the conductive powder within the above range, the slurry can have better conductivity and meet the requirements of the battery for electrode performance. In addition, ensure that the content of conductive powder is not too low, so as to avoid the increase of volume resistivity caused by poor contact between powders. At the same time, prevent the conductive powder content from being too high, resulting in the powder being unable to be evenly dispersed in the slurry, increasing the viscosity of the slurry, affecting its fluidity, and thus affecting the uniformity and precision of printing.
[0046] In some embodiments of the present application, the conductive powder includes at least one of silver powder and silver-coated metal powder. The silver-coated metal powder refers to a silver-coated powder in which silver is coated on the surface of a powder formed of a conductive material other than silver, without any particular limitation. For example, the silver-coated metal powder may be silver-coated copper powder, silver-coated copper alloy powder, silver-coated nickel powder, silver-coated aluminum powder, etc. Thus, it is possible to ensure that the slurry has excellent conductive properties.
[0047] In some embodiments of the present application, the conductive powder includes the silver powder and the silver-coated metal powder, and the mass ratio of the silver powder to the silver-coated metal powder is (20:80)-(30:70). For example, it can be 20:80, 22:78, 24:76, 25:75, 27:73, 30:70. Therefore, by making the mass ratio of the silver powder to the silver-coated metal powder within the above range, it is possible to effectively reduce the material cost while ensuring that the slurry has excellent conductive properties. In addition, it avoids the insufficient density of the solidified material (such as electrodes, wiring, etc.) that may be caused by too low silver powder content, resulting in poor conductivity; and prevents the silver powder content from being too high to increase the cost. In some embodiments of the present application, the conductive powder includes silver powder and silver-coated copper powder.
[0048] In some embodiments of the present application, the specific shape of the conductive powder is not particularly limited, and any of the silver powder and the silver-coated metal powder may be spherical or quasi-spherical (granular), or may be flake or plate-shaped. The silver powder and the silver-coated metal powder are not particularly limited, and may be known and commercially available.
[0049] In some embodiments of the present application, the specific physical properties of the conductive powder are not particularly limited, and the average particle size, specific surface area, tap density, etc. thereof can be within the known range.
[0050] For example, the average particle size D of the silver powder is 50The range of the thickness may be 0.1 μm to 1 μm, for example, 0.1 μm, 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, etc., or any range consisting of the above values.
[0051] For example, the BET specific surface area of the silver powder is 0.2 m 2 / g-2.0m 2 / g. For example, it can be 0.2m 2 / g, 0.5m 2 / g, 0.8m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, etc., or may be within the range consisting of any of the above values.
[0052] For example, the tap density of the silver powder is 1.5 g / cm 3 -8g / cm 3 For example, it can be 1.5 g / cm 3 , 2g / cm 3 , 3g / cm 3 , 5g / cm 3 , 6g / cm 3 , 7g / cm 3 , 8g / cm 3 The above-mentioned arbitrary numerical ranges may also be used.
[0053] For example, the average particle size D of the silver-coated metal powder is 50 The diameter may be in the range of 2 μm to 10 μm, for example, 2 μm, 4 μm, 5 μm, 8 μm, 10 μm, etc., or in the range consisting of any of the above values.
[0054] For example, the BET specific surface area of the silver-coated metal powder is 0.2 m 2 / g-2.0m 2 / g. For example, it can be 0.2m 2 / g, 0.5m 2 / g, 0.8m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, etc., or may be within the range consisting of any of the above values.
[0055] For example, the tap density of the silver-coated metal powder is, for example, 1.5 g / cm 3 -8g / cm 3 For example, it can be 1.5g / cm 3, 2g / cm 3 , 3g / cm 3 , 5g / cm 3 , 6g / cm 3 , 7g / cm 3 , 8g / cm 3 The above-mentioned arbitrary numerical ranges may also be used.
[0056] In some embodiments of the present application, when the silver-coated metal powder is selected as silver-coated copper powder, there is no particular restriction on the amount of silver coating. When the mass of the metal powder in the silver-coated state is taken as 100%, the amount of silver coating can be, for example, in the range of 5%-15%. For example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc., or it can be a range composed of any of the above values.
[0057] In some embodiments of the present application, based on the total mass of the slurry, the mass proportion of the thermosetting component is 1%-10%. For example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., or it can be a range composed of any of the above numerical values. Therefore, by making the mass proportion of the thermosetting component within the above range, the slurry can have better anti-corrosion performance and better adhesion, so that the slurry forms a uniform and stable film layer after curing, ensuring a firm bond between the electrode and the substrate. In addition, it is avoided that the conductive powder cannot be evenly dispersed due to too little content of the thermosetting component, and the adhesion of the cured product is poor; at the same time, it is avoided that the content of the thermosetting component is too large, causing the conductive powder to have a smaller contact density or poor contact in the cured film layer, resulting in insufficient conductivity, resulting in an increase in volume resistivity.
[0058] In some embodiments of the present application, the thermosetting component includes at least one of a bisphenol epoxy resin and an alicyclic epoxy resin. Among them, the bisphenol epoxy resin has excellent anti-corrosion performance. Using it as a thermosetting component can make the slurry have good anti-corrosion performance, and the solidified material formed after the slurry is cured has an anti-corrosion effect, thereby extending the service life of the battery.
[0059] In some embodiments of the present application, the thermosetting component includes the bisphenol epoxy resin and the alicyclic epoxy resin, and the mass ratio of the bisphenol epoxy resin to the alicyclic epoxy resin is (60:40)-(80:20). For example, it can be 60:40, 62:38, 70:30, 76:24, 80:20, etc., or can be a range composed of any of the above values. By making the mass ratio of bisphenol epoxy resin and alicyclic epoxy resin within the above range, the slurry can have good anti-corrosion performance and good adhesion, and can firmly adhere the slurry to the substrate, avoiding the situation where the bisphenol epoxy resin content is too low and cannot exert good anti-corrosion performance and the reliability of the solidified material (such as electrode) formed after the slurry is cured is poor, or the slurry fluidity is too high due to the strong content, causing printing overflow, which is not conducive to the thinning of the grid line, and avoiding the situation where the solidified material due to the high alicyclic epoxy resin content is insufficient in rigidity and low hardness, or the solidified material due to the low alicyclic epoxy resin content is too brittle and the microstructure is easy to crack.
[0060] The specific types and structures of the bisphenol epoxy resin and alicyclic epoxy resin involved in the present application are not particularly limited. They are well-known to those skilled in the art and can be selected according to specific needs.
[0061] Exemplarily, the bisphenol epoxy resin includes, but is not limited to, at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, hydrogenated bisphenol A epoxy resin, and hydrogenated bisphenol F epoxy resin.
[0062] Exemplarily, the alicyclic epoxy resin is an alicyclic type synthesized by oxidation of olefins, etc. For example, the alicyclic epoxy resin can be at least one of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, bis(7-oxabicyclo[4.1.0]3-heptylmethyl)adipate, tetrahydrophthalic acid diglycidyl ester, and hexahydrophthalic acid diglycidyl ester.
[0063] In some embodiments of the present application, based on the total mass of the slurry, the mass proportion of the curing agent is 0.2%-1.5%. For example, it can be 0.2%, 0.5%, 0.7%, 1%, 1.2%, 1.5%, etc., or it can be a range composed of any of the above numerical values. Thus, by making the mass proportion of the curing agent within the above range, the thermosetting component can be prompted to undergo a curing reaction, thereby prompting the slurry to change from a liquid or semi-solid state to a solid state. In addition, it is necessary to avoid too low a curing agent content, which leads to incomplete curing or a long time to complete curing, and at the same time avoid too high a curing agent content, which leads to a slurry storage time that is too short and does not meet the storage requirements.
[0064] In some embodiments of the present application, the curing agent includes at least one of a thermal cationic curing agent and a blocked polyisocyanate curing agent, thereby promoting the curing reaction of the thermal curing component, thereby causing the slurry to transform from a liquid or semi-solid state to a solid state.
[0065] In some embodiments of the present application, the curing agent includes the thermal cationic curing agent and the blocked polyisocyanate curing agent. Wherein, based on the total mass of the slurry, the mass proportion of the thermal cationic curing agent is 0.1%-1%, and the mass proportion of the blocked polyisocyanate curing agent is 0.1%-0.5%. Thus, by controlling the mass proportion of the thermal cationic curing agent and the blocked polyisocyanate curing agent, the thermal curing component can undergo a curing reaction faster, and the conductive paste can have a longer storage time. In addition, it is avoided that the thermal curing component is not completely cured or takes a long time to complete the curing due to too little thermal cationic curing agent content, and the storage time of the conductive paste is too short due to too high content, which does not meet the storage requirements; avoid the blocked polyisocyanate curing agent content is too low, resulting in a decrease in the curing shrinkage rate of the thermal curing component, a weakened aggregation effect on the metal powder, a decrease in conductivity, and a high content of the thermal curing component The shrinkage rate is too high, causing the problem of poor contact between the cured product and the substrate.
[0066] Illustratively, the mass proportion of the thermal cationic curing agent can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or can be a range consisting of any of the above values.
[0067] For example, the mass percentage of the blocked polyisocyanate curing agent may be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, or may be a range consisting of any of the above values.
[0068] In some embodiments of the present application, the blocked polyisocyanate curing agent is a compound formed by blocking a polyisocyanate compound. According to the embodiments of the present application, there is no particular limitation on the blocking agent of the polyisocyanate compound, and imidazoles, phenols, oximes, etc. can be used appropriately.
[0069] In some embodiments of the present application, the polyisocyanate compound includes at least one of aromatic isocyanate and aliphatic polyisocyanate. According to an embodiment of the present application, the aromatic isocyanate includes but is not limited to at least one of toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, dimethyl biphenyl diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, etc. According to an embodiment of the present application, the aliphatic polyisocyanate includes but is not limited to at least one of hexamethylene diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, dicyclohexylmethane diisocyanate, octamethylene diisocyanate, trimethyl hexamethylene diisocyanate, etc.
[0070] It should be noted that the "blocked polyisocyanate curing agent" described in the present application can be purchased or homemade, and the present application conducts relevant experiments by using the purchased blocked polyisocyanate curing agent.
[0071] In some embodiments of the present application, the thermal cationic curing agent includes at least one of a thermal cationic curing agent containing nitrogen atoms and a thermal cationic curing agent containing fluorine atoms. According to an embodiment of the present application, the thermal cationic curing agent includes but is not limited to at least one of boron trifluoride ethyl ether, boron trifluoride phenol, boron trifluoride piperidine, boron trifluoride acetate, boron trifluoride monomethylamine, boron trifluoride monoethylamine, boron trifluoride triethanolamine, and boron trifluoride monoethanolamine.
[0072] In some embodiments of the present application, the slurry may further include an auxiliary agent as required. According to an embodiment of the present application, the auxiliary agent includes at least one of a silane coupling agent, a stabilizer, a dispersant, and an epoxy diluent.
[0073] It should be noted that the present application does not specifically limit the amount of additives added, and those skilled in the art may add them according to specific needs, as long as they can function after addition and do not affect the normal effects of other ingredients.
[0074] In some embodiments of the present application, the specific type of the silane coupling agent is not particularly limited, for example, it can be any one or more of epoxy silane coupling agents, amino silane coupling agents and methacryloxy silane coupling agents. In some embodiments of the present application, the specific type of the stabilizer is not particularly limited, for example, it can be any one or more of polyamide wax, polyethylene wax, fumed silica, etc. In some embodiments of the present application, the specific type of the dispersant is not particularly limited, for example, it can be amides such as stearamide, oleamide, vinyl bisstearamide, etc. In some embodiments of the present application, the specific type of the epoxy diluent is not particularly limited, for example, it can be one of trimethylolpropane triglycidyl ether, o-phenyl glycidyl ether, p-tert-butylphenyl glycidyl ether, ethylene glycol diglycidyl ether, and polypropylene glycol diglycidyl ether.
[0075] In some embodiments of the present application, the viscosity of the slurry is 50Pa·s-600Pa·s, for example, 50Pa·s, 100Pa·s, 200Pa·s, 300Pa·s, 400Pa·s, 500Pa·s, 600Pa·s, etc., or a range consisting of any of the above values.
[0076] In some embodiments of the present application, the viscosity of the slurry at a temperature of 25° C. and a rotation speed of 10 rpm is 200 Pa·s-350 Pa·s. For example, it may be 200 Pa·s, 220 Pa·s, 250 Pa·s, 280 Pa·s, 300 Pa·s, 320 Pa·s, 350 Pa·s, etc., or may be a range consisting of any of the above values.
[0077] Method for preparing slurry
[0078] The present application proposes a method for preparing a slurry. According to an embodiment of the present application, the method comprises: mixing a conductive powder, a thermosetting component, a curing agent and a mixed solvent; grinding the mixed product to obtain the slurry; wherein the mixed solvent comprises two or more solvents with different wettability and different boiling points. By adopting the method described in the present application, a slurry with high plasticity can be prepared. The slurry can be used for printing to make the line type full and not collapsed, and the aspect ratio of the printing can be improved, thereby improving the photoelectric conversion efficiency of the battery; in addition, the slurry can adapt to 18 micron and finer screen openings to achieve fine printing. Those skilled in the art can understand that this method has all the characteristics and advantages of the slurry described above, and will not be elaborated on here.
[0079] The preparation method of the conductive paste involved in the present application is not particularly limited, and a method known in the field of conductive paste can be appropriately used. As a representative example, a method of mixing the above-mentioned components according to a predetermined mixing ratio (quality standard) and premixing using a known mixing device can be cited. Examples of the mixing device include a planetary mixer, a three-roll mill, and the like.
[0080] It should be noted that, in the slurry involved in the present application, in addition to the above-mentioned components such as conductive powder, thermosetting component, curing agent, solvent, and auxiliary agent, various additives known in the field of conductive paste compositions may also be contained as needed. There is no particular limitation on the additives, and specifically, for example, leveling agents, antioxidants, defoaming agents, viscosity modifiers, etc. These additives can be added within the range that does not hinder the effects of the present application specification.
[0081] application
[0082] The present application proposes an electrode. According to an embodiment of the present application, the electrode is formed by curing the slurry obtained by the aforementioned slurry or the aforementioned method. As mentioned above, the slurry of the present application has a high plasticity, which can improve the aspect ratio of the printing to more than 0.5, thereby improving the conductivity of the electrode formed after the slurry is cured, thereby improving the photoelectric conversion efficiency of the battery. Those skilled in the art can understand that the electrode has all the characteristics and advantages of the slurry described above, and will not be repeated here.
[0083] The method of patterning the electrode prepared by the slurry of the present application is not particularly limited, and various known formation methods can be appropriately used. Representatively, screen printing can be cited, and printing methods such as gravure printing, offset printing, inkjet, dispenser, and immersion can also be appropriately used.
[0084] The slurry of the present invention can be widely used in the formation of very precise electrodes, wirings, etc. or the bonding of electronic components, etc. Specifically, for example, it can be appropriately used in the following applications: the collector of a solar cell; the internal electrode or external electrode of a chip-type electronic component; the electrode, wiring or bonding of components used in electromagnetic wave shielding, vibrator bonding, membrane switches, touch panels, etc.; and is more suitable for the collector of a solar cell.
[0085] The present application proposes a battery. According to an embodiment of the present application, the battery includes the aforementioned electrode. As mentioned above, the slurry of the present application has a high plasticity, which can improve the aspect ratio of printing to more than 0.5, thereby improving the conductivity of the electrode formed after the slurry is cured, and then the photoelectric conversion efficiency of the battery can be improved. It can be understood by those skilled in the art that the battery has all the features and advantages of the aforementioned electrode, and no further elaboration is given here.
[0086] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0087] Example 1
[0088] (1) Preparation of slurry: 21 parts of silver powder (D 50 =0.3μm, BET specific surface area =0.2m 2 / g, tap density = 4.2g / cm 3 )、73 parts of silver-coated copper powder (D 50 =4μm, BET specific surface area = 0.3m 2 / g, tap density = 4.5g / cm 3 ), 1 part of bisphenol F epoxy resin, 0.4 parts of alicyclic epoxy resin (tetrahydrophthalic acid diglycidyl ester), 0.8 parts of epoxy diluent (trimethylolpropane triglycidyl ether), 1.0 parts of thermal cationic curing agent (boron trifluoride monoethanolamine), 0.2 parts of blocked isocyanate curing agent (diphenylmethane diisocyanate), 1 part of the first solvent (2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester), 1.5 parts of the second solvent (diethylene glycol butyl ether acetate), 0.1 parts of dispersant (oleic acid amide). After premixing with a planetary stirring degassing machine, it is rolled with a three-roll mill to a low-temperature conductive paste with a fineness of less than 5μm and a viscosity in the range of 200-350Pa·s.
[0089] (2) Preparation of solar cell units: The slurry was printed on a TCO / Si (transparent conductive oxide film and silicon) substrate using a screen printer at a blade pressure of 0.18 MPa and a printing speed of 300 mm / s according to the design pattern of the heterojunction solar cell unit, dried at 170°C and cured at 200°C to form heterojunction solar cell units, a total of 200 pieces.
[0090] Example 2
[0091] A solar cell unit was prepared according to the method described in Example 1, except that 0.25 parts of the first solvent (2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester) and 2.25 parts of the second solvent (diethylene glycol butyl ether acetate) were added during the preparation of the slurry.
[0092] Example 3
[0093] A solar cell unit was prepared according to the method described in Example 1, except that 0.5 parts of the first solvent (2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester) and 2 parts of the second solvent (diethylene glycol butyl ether acetate) were added during the preparation of the slurry.
[0094] Example 4
[0095] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 2 parts of the first solvent (2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester) and 0.5 parts of the second solvent (diethylene glycol butyl ether acetate) were added.
[0096] Example 5
[0097] A solar cell unit was prepared according to the method described in Example 1, except that during the preparation of the slurry, 2.25 parts of the first solvent (2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester) and 0.25 parts of the second solvent (diethylene glycol butyl ether acetate) were added.
[0098] Example 6
[0099] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 1 part of the first solvent (carbitol butyl ether acetate) and 1.5 parts of the second solvent (diethylene glycol butyl ether acetate) were added.
[0100] Example 7
[0101] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 1 part of the first solvent (tripropylene glycol monobutyl ether) and 1.5 parts of the second solvent (3-hydroxy-3-carboxytributyl glutarate) were added.
[0102] Example 8
[0103] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 1 part of the first solvent (tripropylene glycol methyl ether) and 1.5 parts of the second solvent (3-hydroxy-3-carboxytributyl glutarate) were added.
[0104] Example 9
[0105] A solar cell unit was prepared according to the method described in Example 1, except that during the preparation of the slurry, 1 part of the first solvent (2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester) and 1.5 parts of the third solvent (diethylene glycol diethyl ether) were added.
[0106] Example 10
[0107] A solar cell unit was prepared according to the method described in Example 1, except that during the preparation of the slurry, 1 part of the first solvent (2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester) and 1.5 parts of the third solvent (butyl carbitol (diethylene glycol monobutyl ether)) were added.
[0108] Embodiment 11
[0109] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 1 part of the first solvent (carbitol butyl ether acetate) and 1.5 parts of the third solvent (methyl ethyl ketone) were added.
[0110] Example 12
[0111] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 1 part of the first solvent (tripropylene glycol monobutyl ether) and 1.5 parts of the third solvent (pinene alcohol) were added.
[0112] Embodiment 13
[0113] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 1 part of the second solvent (butyl acetate) and 1.5 parts of the third solvent (diethylene glycol diethyl ether) were added.
[0114] Embodiment 14
[0115] A solar cell unit was prepared according to the method described in Example 1, except that during the preparation of the slurry, 1 part of the second solvent (butyl diglycol acetate) and 1.5 parts of the third solvent (butyl carbitol (butyl diglycol ether)) were added.
[0116] Embodiment 15
[0117] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 1 part of the second solvent (tributyl 3-hydroxy-3-carboxyglutarate) and 1.5 parts of the third solvent (methyl ethyl ketone) were added.
[0118] Example 16
[0119] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 0.5 parts of the first solvent (2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester), 0.5 parts of the second solvent (diethylene glycol butyl ether acetate), and 1.5 parts of the third solvent (diethylene glycol diethyl ether) were added.
[0120] Embodiment 17
[0121] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 0.5 parts of the first solvent (2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester), 0.5 parts of the second solvent (3-hydroxy-3-carboxyglutaric acid tributyl ester), and 1.5 parts of the third solvent (butyl carbitol (diethylene glycol monobutyl ether)) were added.
[0122] Embodiment 18
[0123] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 0.5 parts of the first solvent (tripropylene glycol monobutyl ether), 0.5 parts of the second solvent (3-hydroxy-3-carboxyglutaric acid tributyl ester), and 1.5 parts of the third solvent (cyclohexanone) were added.
[0124] Comparative Example 1
[0125] A solar cell unit was prepared according to the method described in Example 1, except that 2.5 parts of the first solvent (2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester) were added during the preparation of the slurry.
[0126] Comparative Example 2
[0127] A solar cell unit was prepared according to the method described in Example 1, except that 2.5 parts of a second solvent (butyl diglycol acetate) was added during the preparation of the slurry.
[0128] Comparative Example 3
[0129] A solar cell unit was prepared according to the method described in Example 1, except that 2.5 parts of a third solvent (diethylene glycol diethyl ether) was added during the preparation of the slurry.
[0130] Comparative Example 4
[0131] A solar cell unit was prepared according to the method described in Example 1, except that during the preparation of the slurry, 1 part of the first solvent (carbitol butyl ether acetate) and 1.5 parts of the first solvent (2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester) were added.
[0132] Comparative Example 5
[0133] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 1 part of the second solvent (tributyl 3-hydroxy-3-carboxyglutarate) and 1.5 parts of the second solvent (butyl diglycol acetate) were added.
[0134] Comparative Example 6
[0135] A solar cell unit was prepared according to the method described in Example 1, except that, during the preparation of the slurry, 1 part of the third solvent (diethylene glycol diethyl ether) and 1.5 parts of the second solvent (butyl carbitol (diethylene glycol monobutyl ether)) were added.
[0136] The differences between Examples 1-18 and Comparative Examples 1-6 are shown in Table 1.
[0137] Table 1
[0138]
[0139]
[0140]
[0141] Performance Testing
[0142] 1. The viscosity test method is: take the slurry as the sample, the viscosity test is a rotational viscometer, 25℃, S14 rotor, when the speed is 10r / min, the reading time is 4min;
[0143] 2. Volume resistivity test: Use a four-probe ohmmeter to test the resistance at both ends of the electrode. The electrode is a heterojunction battery formed by a TCO substrate printed with slurry. The specific measurement process is: use a resistor to test the resistance between two points, and then use a 3D microscope to test the width, height and cross-sectional area of the gate line, and calculate the volume resistivity result according to the following formula:
[0144] Volume resistivity = resistance / grid length × grid cross-sectional area / 100 = line resistance × grid cross-sectional area / 100
[0145] 3. Aspect ratio test: Use a 3D microscope to test the line width and line height of the grid line and calculate the aspect ratio.
[0146] The battery cells prepared in Examples 1-18 and Comparative Examples 1-6 were subjected to parameter tests according to the above method, and the average values were calculated. The specific results are shown in Table 2. From the data in the table, it can be seen that the slurry printing performance of the combined solvent system with different wettability and different boiling points is higher than that of the slurry of the single solvent system or the combined solvent system with the same wettability and the same boiling point. It can be seen from the comparison between the examples and the comparative examples that the slurry of the combined solvent system with different wettability and different boiling points can effectively improve the aspect ratio, improve the shaping performance of the slurry, reduce the volume resistivity, and thus improve the photoelectric conversion efficiency of the battery.
[0147] Table 2
[0148]
[0149]
[0150] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A slurry, characterized in that: include: Conductive powder, thermosetting component, curing agent and mixed solvent, The mixed solvent includes two or more solvents with different wettability and different boiling points.
2. The slurry according to claim 1, characterized in that Based on the total mass of the slurry, the mass proportion of the mixed solvent is 2%-10%; And / or, based on the total mass of the slurry, the mass proportion of the conductive powder is 92%-94%; And / or, based on the total mass of the slurry, the mass proportion of the thermosetting component is 1%-10%; And / or, based on the total mass of the slurry, the mass proportion of the curing agent is 0.2%-1.5%.
3. The slurry according to claim 2, characterized in that The mixed solvent includes at least two of the first solvent, the second solvent, and the third solvent; The diffusion radius of the first solvent on the battery cell is less than 0.9 cm, and the boiling point is higher than 245° C.; The diffusion radius of the second solvent on the battery cell is 0.9-1.1 cm, and the boiling point is 225°C-245°C; The diffusion radius of the third solvent on the battery cell is higher than 1.1 cm, and the boiling point is lower than 225° C.
4. The slurry according to claim 3, characterized in that The first solvent includes at least one of carbitol butyl ether acetate, divalent acid ester, 2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester, tripropylene glycol monobutyl ether, and tripropylene glycol methyl ether; And / or, the second solvent comprises glycol ether acetate, and optionally, the glycol ether acetate comprises at least one of 3-hydroxy-3-carboxyglutarate tributyl ester and diethylene glycol butyl ether acetate; And / or, the third solvent includes at least one of terpineol, diethylene glycol diethyl ether, butyl carbitol (diethylene glycol monobutyl ether), cyclohexanone, and methyl ethyl ketone.
5. The slurry according to any one of claims 1 to 4, characterized in that: The slurry further includes an auxiliary agent.
6. The slurry according to any one of claim 5, characterized in that The conductive powder includes at least one of silver powder and silver-coated metal powder; and / or, the thermosetting component comprises at least one of a bisphenol epoxy resin and an alicyclic epoxy resin; And / or, the curing agent includes at least one of a thermal cationic curing agent and a blocked polyisocyanate curing agent; And / or, the auxiliary agent includes at least one of a silane coupling agent, a stabilizer, a dispersant, and an epoxy diluent.
7. The slurry according to claim 6, characterized in that The conductive powder includes the silver powder and the silver-coated metal powder, and the mass ratio of the silver powder to the silver-coated metal powder is (20:80)-(30:70); And / or, the thermosetting component comprises the bisphenol epoxy resin and the alicyclic epoxy resin, and the mass ratio of the bisphenol epoxy resin to the alicyclic epoxy resin is (60:40)-(80:20); And / or, the curing agent comprises a thermal cationic curing agent and the blocked polyisocyanate curing agent, wherein, based on the total mass of the slurry, the mass proportion of the thermal cationic curing agent is 0.1%-1%, and the mass proportion of the blocked polyisocyanate curing agent is 0.1%-0.5%; And / or, the blocked polyisocyanate curing agent is a compound formed by blocking a polyisocyanate compound.
8. A method for preparing the slurry according to any one of claims 1 to 7, characterized in that: include: The conductive powder, the thermosetting component, the curing agent and the mixed solvent are mixed; Grinding the mixed product to obtain the slurry; The mixed solvent includes two or more solvents with different wettability and different boiling points.
9. An electrode, characterized in that: The method is formed by solidifying the slurry prepared by the slurry described in any one of claims 1 to 7 or the method described in claim 8.
10. A battery, characterized in that: Comprising the electrode according to claim 9.